Identification of Alternative Mitochondrial Electron Transport Pathway Components in Chickpea Indicates a Differential Response to Salinity Stress between Cultivars - Sweetman, Crystal; Miller, Troy K.; Booth, Nicholas J.; Shavrukov, Yuri; Jenkins, Colin L.D.; Soole, Kathleen L.; Day, David A. (International journal of molecular sciences, 2020)
All plants contain an alternative electron transport pathway (AP) in their mitochondria, consisting of the alternative oxidase (AOX) and type 2 NAD(P)H dehydrogenase (ND) families, that are thought to play a role in controlling oxidative stress responses at the cellular level. These alternative electron transport components have been extensively studied in plants like Arabidopsis and stress inducible isoforms identified, but we know very little about them in the important crop plant chickpea. Here we identify AP components in chickpea (Cicer arietinum) and explore their response to stress at the transcript level. Based on sequence similarity with the functionally characterized proteins of Arabidopsis thaliana, five putative internal (matrix)-facing NAD(P)H dehydrogenases (CaNDA1-4 and CaNDC1) and four putative external (inter-membrane space)-facing NAD(P)H dehydrogenases (CaNDB1-4) were identified in chickpea. The corresponding activities were demonstrated for the first time in purified mitochondria of chickpea leaves and roots. Oxidation of matrix NADH generated from malate or glycine in the presence of the Complex I inhibitor rotenone was high compared to other plant species, as was oxidation of exogenous NAD(P)H. In leaf mitochondria, external NADH oxidation was stimulated by exogenous calcium and external NADPH oxidation was essentially calcium dependent. However, in roots these activities were low and largely calcium independent. A salinity experiment with six chickpea cultivars was used to identify salt-responsive alternative oxidase and NAD(P)H dehydrogenase gene transcripts in leaves from a three-point time series. An analysis of the Na:K ratio and Na content separated these cultivars into high and low Na accumulators. In the high Na accumulators, there was a significant up-regulation of CaAOX1, CaNDB2, CaNDB4, CaNDA3 and CaNDC1 in leaf tissue under long term stress, suggesting the formation of a stress-modified form of the mitochondrial electron transport chain (mETC) in leaves of these cultivars. In particular, stress-induced expression of the CaNDB2 gene showed a striking positive correlation with that of CaAOX1 across all genotypes and time points. The coordinated salinity-induced up-regulation of CaAOX1 and CaNDB2 suggests that the mitochondrial alternative pathway of respiration is an important facet of the stress response in chickpea, in high Na accumulators in particular, despite high capacities for both of these activities in leaf mitochondria of non-stressed chickpeas.